Development of a tool for comprehensive evaluation of population-based cancer registries. (September 2018) - Sheikhtaheri, Abbas; Nahvijou, Azin; Sedighi, Zahra; Hadji, Maryam; Golmahi, Mohammad; Roshandel, Gholamreza; Beiki, Omid; Ravankhah, Zahra; Zendehdel, Kazem
Highlights: Population-based cancer registries should be evaluated comprehensively with regards to their inputs, processes and outputs. There are few comprehensive tools for comprehensive evaluation of population-based cancer registries, especially in low- and middle-income countries. A comprehensive evaluation tool was developed for population-based cancer registry and can be tailored for other countries. This tool is used to evaluate guidelines, analysis and reports, governance and infrastructure, information technology, personnel knowledge, practice and data quality. Abstract: Objective: Several methods have been suggested for evaluation of population-based cancer registries (PBCR) worldwide. However, most of these methods evaluate the data and outputs of the cancer registries. This study aimed to develop a comprehensive tool and protocol for evaluation of inputs, processes and outputs of a PBCR. Methods: The standards of the North American Association of Central Cancer Registries (NAACCR) were used to draft a comprehensive checklist. In addition, the national guidelines of PBCR were used to develop a questionnaire for evaluation of knowledge and practice of the PBCR personnel. Furthermore, a protocol for evaluation of the completeness and validity of the PBCR data was developed according to the International Agency for Research on Cancer (IARC) and the NAACCR guidelines. A 0–4 Likert based score and expert opinions (10 experts) were used to assess validity of the eight questionnaires/checklists. A modified Delphi method was applied to validate the checklists and questionnaires. Questions with a score higher than 3 remained in the final tools. Results: The final package consists of 546 questions including 108 (19.8%) for evaluation of guidelines, 54 (9.9%) for analysis and reports, 87 (15.9%) for governance and infrastructure, 155 (28.4%) for information technology, 21 (3.8%) for personnel knowledge and 121 (22.2%) for their practice. Additionally, data quality indicators were also considered for evaluation of PBCRs. Conclusion: This comprehensive tool can be used to show the gaps and limitations of the PBCR programs and provide informative clues for their improvement.